Blanching-Induced Changes in Polyphenol Oxidase, Antioxidants and Phenolic Profile of Mangosteen Pericarp - Giroon Ijod; Nur Izzati Mohamed Nawawi; Rabiha Sulaiman; Noranizan Mohd Adzahan; Farooq Anwar; Ezzat Mohamad Azman (Food Technology and Biotechnology)
Research background. Anthocyanin pigments in mangosteen pericarp can serve as natural colourants; however, their stability is compromised by enzymatic browning caused by polyphenol oxidase (PPO). Thus, this study aims to investigate how hot water and steam blanching affect the PPO activity, phenolic profile and antioxidant properties of mangosteen pericarp. Experimental approach. Fresh mangosteen pericarp was blanched in hot water or steam at 100 °C for 0, 30, 60, 90 and 120 s and the residual PPO activity, total phenolic content (TPC), total anthocyanins, antioxidant activity, browning index and colour properties were evaluated. Additionally, the phenolic compounds were identified using liquid chromatography-mass spectrometry (LC-MS). Results and conclusions. Zero-order reaction kinetics (R2>0.800) showed that residual PPO activity was significantly (p<0.05) reduced in both blanched and steamed mangosteen pericarp. As expected, PPO was inactivated more rapidly in hot water (t1/2=59.0 s) than in steam blanching (t1/2=121.1 s). However, the principal component analysis (PCA) showed that steam blanching for 90 s was the most efficient method, preserving the highest levels of antioxidant capacity, expressed as Trolox equivalents (TE; 9135 µmol/g), Fe(III)-reducing power, expressed as TE, (9729 µmol/g), total anthocyanins (3.03 mg/g), and TPC, expressed as gallic acid equivalents (1057 mg/g). Overall, steam blanching for 90 s was the most efficient method because it best preserved the phenolic compounds and is also a cost-effective method compared to hot water, which needs to be replaced after a few applications. Novelty and scientific contribution. This is the first study to report the effects of blanching on the anthocyanins mainly present in mangosteen pericarp, in particular cyanidin-3-O-sophoroside (C3S) and cyanidin-3-O-glucoside (C3G), using high-performance liquid chromatography (HPLC) and LC-MS. This study makes a significant scientific contribution to the food industry by providing suitable blanching methods to preserve the quality of bioactive compounds, especially anthocyanins in mangosteen pericarp, which can be used as a natural colourant.